Child Maltreatment and the Child Welfare System as Environmental Factors in the International Classification of Functioning - Kim, Katherine; Moss, Corinne; Park, Jane Jungyoon; Wekerle, Christine (Frontiers in Rehabilitation Sciences, 2022)
The WHO defines child maltreatment as any form of neglect, exploitation, and physical, emotional, or sexual abuse, committed against children under the age of 18. Youth involved in the child welfare system report more maltreatment experiences and environmental turbulence (e.g., number of moves, caseworkers), placing them at greater risk for poorer physical and mental health. The International Classification of Functioning, Disability, and Health (ICF) provides a framework to describe health conditions and severity of disabilities for an individual and/or group in the context of environmental factors. The Maltreatment and Adolescent Pathways (MAP) study is a longitudinal study, assessing self-reports on variables (e.g., child maltreatment history, trauma symptoms, dating violence, and substance use) of youth in an urban child protection service system. This study focuses on 11 of the 24 MAP publications that pertain to health and functioning, which can be considered applicable to the ICF framework, following established linking rules. The purpose of this study is to analyze these MAP sub-studies, with maltreatment and involvement in the child welfare system as environmental factors that impact the functioning of child welfare-involved youth. Findings indicate significant relationships across environmental factors (i.e., child maltreatment histories, child welfare system involvement), health conditions (i.e., trauma symptomatology, psychological distress, intellectual disabilities), and functioning problems (i.e., substance use, adolescent dating violence, sexual risk-taking, coping motives, sleep problems). The interrelated nature of these factors in the MAP sub-studies suggests the value of the ICF model to a holistic health view of use to practitioners supporting system-involved youth, clarifying unattended environmental factors in guiding service provision for foster care and/or maltreated youth.